Analisis Gugus Fungsi dan Sifat Termal Limbah Jaring Ikan Untuk Produk Otomotif - Aryanti, Fitria Ika; Silvia, Silvia; Santoso, Teguh Budi; Romaro, Alana Lovin (Program Studi Teknik Kimia, Universitas Pamulang, 2024)
Plastic has been used in daily life due to its durability. Fishing net waste is a type of plastic waste that is dangerous. Fishing net waste can also damage marine biota, such as coral reefs and marine animals. One type of polyamide that is widely used is nylon. Fishing net waste containing nylon has the potential to be recycled. In this research, fishing net waste is used for automotive product applications using a twin-screw extruder. There are five variations: pure polyamide (PA), recycled polyamide (rPA), PA-rPA 50:50, PA-rPA 75:25, and PA-rPA 25:75. To be able to determine the characteristics of the mixed product, several tests were carried out, including testing the thermal properties of the final product with DSC and FTIR testing to identify functional groups. Based on the research results, it was found that all variations contained polyamide polymers, which were characterized by a melting temperature of 218.8â€“224.4 °C and obtained carbonyl functional groups (C=O) and secondary amine functional groups (Nâ€“H) in the FTIR test results, which indicated the presence of amide bonds in the samples.